Effects of Omalizumab on FcεRI and IgE Expression in Lesional Skin of Bullous Pemphigoid - Seyed Jafari, S. Morteza; Gadaldi, Karolina; Feldmeyer, Laurence; Yawalkar, Nikhil; Borradori, Luca; Schlapbach, Christoph (Frontiers in Immunology, 2019)
Recent animal and human studies suggest an important role of immunoglobulin E (IgE) as an alternative pathogenic pathway in the development of bullous pemphigoid (BP). Use of anti-IgE targeted therapies, such as omalizumab, has been shown successful in recent studies. The aim of this study was to investigate the mechanism of action of omalizumab in BP. We report two cases of BP patients treated with omalizumab. FcεRI and IgE levels in serum and in the skin samples, as well as anti-BP180 and -BP230, eosinophils and basophils in serum were assessed before and during the treatment. Both patients showed a marked improvement after 4 months, with no adverse effects. Down-regulation of FcεRI, IgE in lesional skin and on circulating basophils were observed in parallel with clinical improvement. The current case study supports the role of omalizumab in the treatment of a subset of BP patients. Its efficacy might be related to downregulation of FcεRI and IgE in lesional skin.